(untitled) (GYMNASIUM, 2017)
With this work we want to show that the element of dance, eurhythmy, and body language contributes in the development in children imagination of classes V - VIII. Education of the body language, expressiveness, the use of non-verbal language has rules as strict as those of verbal communication. What is to become the dominant part of mental life pubertal group is social integration, playful behaviors being replaced by the insertion behavior. As methods in the study we used SICA color analysis, static and dynamic analysis of expression. The development of creative thinking and eurhythmy has a lot of benefits in children development, beneficiating both physically and emotionally, cognitively and socially. It is an art, defined by playing sounds and speaking by movements and gestures. In the first phase pedagogical eurhythmy helps children to develop physically. It was later discovered that the transposition of sounds in harmonious movements stimulates thinking, imagination and creativity. The conclusion of the study is that the teenager demonstrates creative thinking and communication skills by training and use of social, verbal and non-verbal outside school.